Construção de um aplicativo para a Biblioteca Setorial Dr. Paulo Bezerra da Escola Multicampi de Ciências Médicas do RN - Cunha Neto, José da (2023)
University libraries, with the advent of information technologies and the change in society's behavior, acquired a new format: digital/electronic. The Dr. Paulo Bezerra sectoral library is part of the Escola Multimpi Ciências Médicas do RN at the Universidade Federal do Rio Grande do Norte (Caicó, RN) and offers services and products to the academic community. Despite using the University's computerized platforms, they are challenges in promoting services and products. Therefore, the objective of this work is to build an application for using the Dr. Paulo Bezerra sectoral library of the Escola Multicampi de Ciências Médicas do RN. To this end, this research is exploratory, applied, qualitative, and a case study and used meetings with the library to gather information about the sectors and their responsibilities, as well as photographic records. The Glide apps website (http://www.glideapps.com) was used to create the interface. Finally, the application was evaluated using the word cloud technique of the application user's reactions through Mentimeter (http://www.mentimeter.com). The product was an application that is available for free download and has a login page and three internal tabs with the deposits "home", "technical team" and "talk to the library". In each tab, there are easy-access resources to search for reference and library information. The application was evaluated by 52 people with different roles at the institution (teachers, students, and technical staff) and demonstrated to be “intuitive”, “practical” and “necessary”. The application brings users closer to the services and products offered by the library, facilitating their academic integration.